Fermented Juice Production from Persimmon (Diospyros kaki) Fruit - Minh Phuoc Nguyen (Journal of Global Pharma Technology, 2016)
Persimmon (Diospyros kaki) reveals beneficial health effects owing to nutritional components and antioxidant capacity. It is a good source of fiber, phenolics, minerals, vitamins and other bioactive compounds. However it’s sensitive to deterioration in a short harvest season. In this study, fermentation of persimmon juice with probiotic bacteria Lactobacillus acidophilus as well as effectiveness of several technical variables in pretreatment and fermentation were investigated. Our results revealed that thermal treatment 650C in 4 minutes and then cooling at 40C in 20 minutes were appropriate for tannin reduction to mild astringent taste. The initial inoculations (108 cfu/ml) of Lactobacillus acidophilus, 8% sugar, pH 4.4, temperature 37oC were suitable for persimmon extract fermentation within 24 hours. Persimmon juice fermented probiotic Lactobacillus acidophilus was highly value for human health.Keywords: Persimmon, Lactobacillus acidophilus, Fermentation, Probiotic, Tannin, Thermal.